Delivering Acceptance and Commitment Therapy for Weight Self-Stigma Through Guided Self-Help: Results From an Open Pilot Trial. Issue 1 (February 2018) - Levin, Michael E.; Potts, Sarah; Haeger, Jack; Lillis, Jason
Abstract: Weight self-stigma is a promising target for innovative interventions seeking to improve outcomes among overweight/obese individuals. Preliminary research suggests acceptance and commitment therapy (ACT) may be an effective approach for reducing weight self-stigma, but a guided self-help version of this intervention may improve broad dissemination. This pilot open trial sought to evaluate the potential acceptability and efficacy of a guided self-help ACT intervention, included coaching and a self-help book, with a sample of 13 overweight/obese individuals high in weight self-stigma. Results indicated a high degree of program engagement (77% completed the intervention) and satisfaction. Participants improved on outcomes over time including weight self-stigma, emotional eating, weight management behaviors, health-related quality of life, and depression. Although not a directly targeted outcome, participants improved on objectively measured weight, with an average of 4.18 pounds lost over 7 weeks, but did not improve on self-reported weight at 3-month follow-up. Processes of change improved over time, including psychological inflexibility, valued action and reasons to lose weight. Coaching effects indicated greater retention and improvements over time with one coach vs. the other, suggesting characteristics of coaching can affect outcomes. Overall, these results provide preliminary support for the acceptability and efficacy of a guided self-help ACT program for weight self-stigma. Implications of these results and how to address clinical challenges with guided self-help are discussed. Highlights: Tested a guided self-help ACT program for self-stigma with 13 obese participants. Found high acceptability and engagement in the guided self-help intervention. Significant improvements in weight self-stigma, health behaviors, and mental health. Significant improvements in ACT processes of change. Almost all treatment effects persisted at 3 month follow up.